Negative nominal interest rates: History and current proposals - Cordelius Ilgmann; Martin Menner (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2011)
Given the renewed interest in negative interest rates as a means for overcoming the zero bound on nominal interest rates, this article reviews the history of negative nominal interest rates and gives a brief survey over the current proposals that received popular attention in the wake of the financial crisis of 2007/08. It is demonstrated that taxing money proposals have a long intellectual history and that instead of being the conjecture of a monetary crank, they are a serious policy proposal. In a second step the article points out that, besides the more popular debate on a Gesell tax as a means to remove the zero bound on nominal interest rates, there is a class of neoclassical search-models that advocates a negative tax on money as efficiency enhancing. This strand of the literature has so far been largely ignored by the policy debate on negative interest rates.
Keywords: 330; negative interest rates; history of economic thought; Silvio Gesell; zero bound; search-theoretical models; monetary policy